For a Place in History:: Explaining Greece’s Revolutionary Organization 17 November - Kassimeris, George (Journal of Conflict Studies, 2007)
Abstract The Revolutionary Organization 17 November (17N) conducted terrorist attacks in Greece for 27 years (1975-2002), making it the most durable of the militant Leftist revolutionary groups that emerged from the European radical milieu of the 1970s. 17N went to great lengths in its communiqués – and eventually in trial testimony – to position itself as the only authentic, progressive political force in post-Junta Greece. In spite of the absence of any demonstrable mass political constituency, 17N’s leaders convinced themselves that they represented the vanguard of political change in the country. But 17N was never an authentic revolutionary group. Instead, it was a clandestine band of disillusioned armed militants with a flair for revolutionary rhetoric and symbolism for whom terrorism had become a way of life: a career. Its members lived in a closed, self-referential world where terrorism became a way of life from which it was impossible to walk away or to confront reality. Feeling themselves to be a genuine instrument of history, 17N leaders believed that it did not matter that there could never be a military victory as long as 17N, ‘intervened’ and ‘resisted.’ For their operational leader, Dimitris Koufodinas, and many of his comrades what was important was the act of ‘resistance’ itself and the notion that blood and death, even one’s own, would carry the mission forward, ultimately securing 17N a place in history.